Pyrene based conjugated materials: synthesis, characterization and electroluminescent properties - Salunke, Jagadish K.; Sonar, Prashant; Wong, F. L.; Roy, V. A. L.; Lee, C. S.; Wadgaonkar, Prakash P. (Physical Chemistry Chemical Physics, 2014)
In this work, three novel pyrene cored small conjugated molecules, namely 1,3,6,8-tetrakis(6-(octyloxy)naphthalene-2-yl) pyrene (PY-1), 1,3,6,8-tetrakis((E)-2-(6-(n-octyloxy) naphthalene-2-yl) vinyl) pyrene (PY-2) and 1,3,6,8-tetrakis((6-(n-octyloxy) naphthalene-2-yl) ethynyl) pyrene (PY-3) have been synthesized by Suzuki, heck and Sonogashira organometallic coupling reactions, respectively. The effects of single, double and triple bonds on their optical, electrochemical, and thermal properties are studied in detail. These all materials are fluorescent and they have been used in organic light-emitting diodes (OLEDs) and their electroluminescent properties have been studied.